Loss of daptomycin susceptibility in clinical Staphylococcus epidermidis infection coincided with variants in WalK. Issue 1 (7th September 2020) - Brazeau, Nicholas F; Levinson, Kara J; Schranz, Asher; Moser, Kara A; Hollis, Ian; Iyer, Prashanth; Chien, Christopher; Bowen, Amanda; van Duin, David; Lachiewicz, Anne; Andermann, Tessa; Jones, Melissa; et al.
Abstract: Daptomycin (DAP) is key in treating multidrug-resistant Staphylococcus infections. Diminished susceptibility to DAP is emerging among Staphylococcus epidermidis strains although mechanisms for non-susceptibility (NS) remain poorly understood. We report a case of persistent S. epidermidis bacteremia in which loss of DAP susceptibility arose during prolonged treatment. Whole genome sequencing identified two mutations, Q371del and P415L, in a single-affected gene, WalK, that coincided with the emergence of DAP-NS. Protein modeling of the mutations predicted a disruption of WalK protein configuration. The emergence of mutations in a single-gene during DAP exposure raises concerns in an era of increasingly treatment-resistant infections. Lay summary: Daptomycin is an important antibiotic for fighting Staphylococcus infections. We identified variants in the WalK gene that were coincident with resistance in a clinical Staphylococcus epidermidis infection. Clinicians, hospital epidemiologists, and microbiology laboratories need to be aware of the potential for the evolution of drug resistance during prolonged daptomycin therapy.